Achieving high-performance pure tungsten by additive manufacturing: Processing, microstructural evolution and mechanical properties. (June 2023) - Hu, Zhangping; Liu, Ye; Chen, Songhua; Liu, Shaocun; Yu, Liming; Liu, Yongchang; Ma, Zongqing
Abstract: It is always a great challenge to manufacture defect-free and high-performance pure tungsten by laser additive manufacturing until now. In this work, using nanopowder as precursors, the pure tungsten green parts were successfully manufactured by indirect additive manufacturing technology, powder extrusion printing. The subsequent debinding-sintering process of the green parts has been optimized to obtain high-relative-density, fine-grain and defect-free tungsten samples. The relative density of the sample increased with the increase of sintering temperature. The microstructures of pure tungsten prepared by direct and indirect additive manufacturing techniques were studied comparatively, including laser powder bed fusion and powder extrusion printing. The formation of microcracks in pure tungsten samples is mainly due to the high residual stress provided by laser powder bed fusion and the high ductile-to-brittle transition temperature characteristics of tungsten. The sintering temperature of the pure tungsten samples with the highest compressive strength (1290 ± 10 MPa) was determined to be 2000 °C. Compared with other sintered samples, defect-free samples sintered at 2000 °C had finer grains (9.8 μm) while maintaining high relative density (99.1 ± 0.4%). The higher strength of the sintered samples at 2000 °C is related to the fine-grain strengthening and high relative density compared to samples obtained from other direct additive manufacturing technologies and sintered at other temperatures. The indirect additive manufacturing technique based on the use of nanopowder precursors developed in this work provides a new technical approach for the additive manufacturing of high-performance tungsten and/or other refractory metals. Highlights: The application of nano-powders for indirect additive manufacturing was innovative. A defect-free and high-performance pure tungsten parts were fabricated. The difference in microstructure of pure tungsten prepared by LPBF and PEP was investigated. The mechanism of mechanical properties of pure tungsten parts was revealed.